2011
DOI: 10.1590/s0006-87052011000400003
|View full text |Cite
|
Sign up to set email alerts
|

A comparative genetic diversity assessment of industrial and household Brazilian cassava varieties using SSR markers

Abstract: This study was carried out in order to assess the genetic diversity of 20 cassava (Manihot esculenta Crantz) genotypes with high phenotypic performance using microsatellite markers. Two groups were considered for this study: eleven varieties for industrial uses and nine for household consumption. By using nine microsatellite primers, high polymorphism was identified in all the loci analyzed, with values reaching 100%. On average, 3.4 alleles per locus were found, with 0.371 the value estimated for the observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
(17 reference statements)
0
5
0
2
Order By: Relevance
“…Previous genetic studies found high genetic diversity into cultivated M. esculenta in different regions of Brazil (Elias et al, 2004;Peroni et al, 2007;Siqueira et al, 2011;Mühlen et al, 2013). High genetic heterozygosity values have been confirmed even in countries outside of the area of domestication of manioc, such as in Puerto Rico (Montero-Rojas et al, 2011), Uganda (Turyagyenda et al, 2012), and Thailand (Fu et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Previous genetic studies found high genetic diversity into cultivated M. esculenta in different regions of Brazil (Elias et al, 2004;Peroni et al, 2007;Siqueira et al, 2011;Mühlen et al, 2013). High genetic heterozygosity values have been confirmed even in countries outside of the area of domestication of manioc, such as in Puerto Rico (Montero-Rojas et al, 2011), Uganda (Turyagyenda et al, 2012), and Thailand (Fu et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…The geographic pattern was considered a minor cause of genetic structure in earlier studies on genetic diversity of traditional manioc varieties (Elias et al, 2004;Siqueira et al, 2011). However, Mühlen et al (2013) identified some geographic structure at K = 3 and K = 4, although these were less significant than the K = 2 sweet-bitter dichotomy, which was also observed by Elias et al (2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Marcadores moleculares, como RAPD (Random Amplified Polymorphic DNA), AFLP (Amplified Fragment Length Polymorphism) e microssatélites têm sido utilizados com sucesso no estudo da variabilidade genética da mandioca (BREECHING et al, 1993;COLOMBO et al, 1998COLOMBO et al, , 2000CARVALHO et al, 2000;ELIAS et al, 2000;SCHAAL, 2001;SCHAAL, 2001;ASSANTE;OFDEI, 2003;FREGENE et al, 2003;ELIAS et al, 2004;LOKKO, et al, 2006;KIZITO et al, 2007;MOYIB et al, 2007;RIMOLDI et al, 2010;SIQUEIRA et al, 2009SIQUEIRA et al, , 2010SIQUEIRA et al, e 2011LEKHA et al, 2011;VIEIRA et al, 2011;ALVES-PEREIRA et al, 2012 SCHAAL et al, 2001;FARALDO et al, 2002;FREGENE et al, 2003;MKUMBIRA et al, 2003;BRESSAN et al, 2004;ELIAS et al, 2004;PERONI et al, 2007;MOYB et al, 2007;ROCHA et al, 2008;PEREIRA, 2008;SIQUEIRA et al, 2009SIQUEIRA et al, , 2010SIQUEIRA et al, , 2011LEKHA et al,. 2011;OLIVEIRA et al, 2012;ALVES-PEREIRA et al, 2012).…”
Section: Marcadores Molecularesunclassified